THE JUSTIFICATION FOR THE PERMANENT RESTRICTION IMPOSED ON THE RIGHT TO BE ELECTED BY LAW 30717 FOR INDIVIDUALS CONVICTED OF TERRORISM CHARGES - Raffo Miranda, José Francisco (2025)
In this research we analyze the justification for the permanent restriction imposed on the right to be elected for individuals convicted of terrorism charges. The balance between ensuring democratic order and respecting fundamental rights is examined. The research concludes that the restrictions are justified and compatible with the Constitution.